Different Effects of SSRIs, Bupropion, and Trazodone on Mitochondrial Functions and Monoamine Oxidase Isoform Activity - Ľupták, Matej; Fišar, Zdeněk; Hroudová, Jana (Antioxidants, 2023)
Mitochondrial dysfunction is involved in the pathophysiology of psychiatric and neurodegenerative disorders and can be used as a modulator and/or predictor of treatment responsiveness. Understanding the mitochondrial effects of antidepressants is important to connect mitochondria with their therapeutic and/or adverse effects. Pig brain-isolated mitochondria were used to evaluate antidepressant-induced changes in the activity of electron transport chain (ETC) complexes, monoamine oxidase (MAO), mitochondrial respiratory rate, and ATP. Bupropion, escitalopram, fluvoxamine, sertraline, paroxetine, and trazodone were tested. All tested antidepressants showed significant inhibition of complex I and IV activities at high concentrations (50 and 100 μmol/L); complex II + III activity was reduced by all antidepressants except bupropion. Complex I-linked respiration was reduced by escitalopram >> trazodone >> sertraline. Complex II-linked respiration was reduced only by bupropion. Significant positive correlations were confirmed between complex I-linked respiration and the activities of individual ETC complexes. MAO activity was inhibited by all tested antidepressants, with SSRIs causing a greater effect than trazodone and bupropion. The results indicate a probable association between the adverse effects of high doses of antidepressants and drug-induced changes in the activity of ETC complexes and the respiratory rate of mitochondria. In contrast, MAO inhibition could be linked to the antidepressant, procognitive, and neuroprotective effects of the tested antidepressants.